ASPEK HUKUM PENDIRIAN DAN PENGESAHAN BADAN USAHA NON BADAN HUKUM - Raendhi Rahmadi (SUPREMASI HUKUM, 2021)
Errors in the establishment of a business entity create fatal legal problems in the future related to the existence and business entity that has been established, this is due to a lack of understanding of the correct application of legality for an established entity, so to anticipate this problem it is necessary to explain the stages major must go through. To explain it, this paper is compiled using descriptive-analytical methods with a normative juridical approach using empirical data. So that from this paper it is hoped that it can answer important things regarding, how to create the entity of organization in national law, especially for a business entity. When is a business entity establishment born and considered to have a legal existence in the Indonesian national legal system. Keywords: existence; establishment; business entity.